New Narratives, Emerging Genres: Dance Film Development in Indonesia - Deny Tri Ardianto,; Jasni Dolah, (Wacana Seni Journal of Arts Discourse, 2018)
Dance film has grown rapidly in Europe and America, while in Indonesia dance film has received little attention from both the general public and the "art world". The questions related to what a dance film is and how a dance film is characterised, still often become the main issues in every discussion forum and festival in Indonesia. This paper seeks to describe and provide insights into and an understanding of, the types of film or video work that can be categorised as dance film or dance documentation. Employing a descriptive qualitative study involving a literature search and interviews with respondents, as the data collection methods from year 2010 to 2017, this study is expected to provide an academic contribution to, as well as to support the development of, dance film. Specifically, it is hoped this research will: (1) enrich the scientific repertoire in the field of creation, (2) complement the genre development in the Indonesian film industry and (3) build people's appreciation in response to the existence of dance film, as a new means of narration and language of expression in the developing field of Indonesian film.